Gender in Agriculture and Climate Response in West Africa - Partey, Samuel T. (2024)
While women constitute at least 40% of the agriculture labour force they often lack substantial access to agricultural inputs, financial credits, labour and land, which are critical for their activities and livelihoods. This situation poses a major threat to food security due to the substantial contributions of women to food production at multiple scales in West Africa. With high aridity and sporadic rainfall patterns, women farmers especially in the Sahel of West Africa become more vulnerable to droughts and suffer high risks of productivity failure due to lack of irrigation facilities.